A high-sublimation fastness disperse red dye composition for polyester-polyamide blended fabric and application thereof
Patent Information
- Application Number
- CN202611142785.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-16
AI Technical Summary
本发明的目的在于提供一种用于涤氨混纺织物的高耐升华牢度分散染料组合物,通过特定结构的染料复配,解决现有技术在深色染色中需酸性染色、还原清洗、升华牢度差、泡洗牢度差、高温沾色及得色量低的问题
(1)本发明发现通过将组分A、组分B、组分C按照特定比例组合使用,产生了预料不到的协同效应,具有协同增效的效果。
Smart Images

Figure CN122917569A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of dye manufacturing and application technology, specifically relating to a disperse red dye composition with high sublimation fastness for polyester-ammonia blended fabrics and its application. Background Technology
[0002] With the development of functional sportswear and fashionable underwear, the application of polyester-spandex blended fabrics is becoming increasingly widespread. However, significant challenges arise when dyeing polyester-spandex blended fabrics in dark colors, such as deep red. First, there is a contradiction between heat setting and sublimation fastness. Polyester-spandex fabrics typically require heat setting at high temperatures of 190℃-210℃ to impart elastic recovery. Traditional azo disperse dyes, such as those of formula I, have bright colors but low dye uptake and poor wash fastness. Furthermore, most of these dyes can only be applied under acidic conditions, increasing the environmental pressure on dyeing wastewater treatment. N-aromatic ring dyes, such as those of formula II, have bright colors and high dye uptake, but poor sublimation fastness. Zhejiang Wanfeng Chemical Co., Ltd. has developed a new type of azo disperse dye (CN121293782A; CN122011802A), as shown in formula III. This dye has deep, vibrant colors and high dye uptake, with good sublimation fastness up to 180℃. However, as the temperature increases, such as at 190℃, sublimation begins, causing changes in fabric color, decreased fastness, and contamination of the spandex component, resulting in "white showing" or color spots.
[0003]
[0004] Structural Formula I
[0005] Structural Form II
[0006] Structural Form III Secondly, there is a contradiction between high fastness and color yield. To improve sublimation fastness, current technology uses dyes with larger molecular weights or stronger polarity. These dyes have good heat resistance, but the dyeing rate is relatively low and the color yield is relatively light. In order to achieve the dyeing purpose, it is usually necessary to significantly increase the amount of dye used, which not only increases the cost, but also leads to floating color and makes the treatment of dyeing and printing wastewater more difficult, making it impossible to achieve "ecological development and green development".
[0007] Third, the limitations of single dyes. Currently, no dye on the market has been found that can simultaneously achieve high wash fastness, high alkali resistance, high sublimation fastness, and a deep color effect. Summary of the Invention
[0008] [Technical Issues] Develop a high-fastness disperse dye or combination that can satisfy the dark color effect, withstand high-temperature heat setting at 210℃, and is suitable for dyeing polyester-ammonia blended fabrics.
[0009] [Technical Solution] The purpose of this invention is to provide a disperse dye composition with high sublimation fastness for polyester-ammonia blended fabrics. By compounding dyes with specific structures, this invention solves the problems of existing technologies in dark-colored dyeing, such as the need for acid dyeing, reduction washing, poor sublimation fastness, poor washing fastness, high-temperature staining, and low color yield.
[0010] To achieve the above objectives, the present invention adopts the following technical solution: A high sublimation fastness disperse red dye composition for polyester-ammonia blended fabrics, wherein the composition comprises 2,4-dinitroaniline as a diazo component and includes at least two of the following disperse dyes: component A, component B, and component C. Component A is an N,N-dibenzylamine azo disperse dye with the following structure: ; Component B is an N-benzyl-N-(4-chloro)benzylamine azo disperse dye with the following structure: ; Component C is an N,N-bis(4-chloro)benzylamine azo disperse dye with the following structure: .
[0011] In one embodiment of the present invention, the disperse red dye composition comprises component A, component B and component C; wherein, by mass percentage, component A is 10% to 40%, component B is 10% to 70%, and component C is 10% to 80%.
[0012] In one embodiment of the present invention, the disperse red dye composition comprises component A, component B and component C; wherein, by mass percentage, component A is 10% to 40%, component B is 10% to 50%, and component C is 20% to 80%.
[0013] In one embodiment of the present invention, the disperse red dye composition comprises, by weight percentage: 20% component A, 50% component B, and 30% component C.
[0014] In one embodiment of the present invention, the disperse red dye composition comprises, by weight percentage: 20% component A, 40% component B, and 40% component C.
[0015] In one embodiment of the present invention, the disperse red dye composition comprises, by weight percentage: 10% component A, 10% component B, and 80% component C.
[0016] In one embodiment of the present invention, the disperse red dye composition comprises, by weight percentage: 40% component A, 30% component B, and 30% component C.
[0017] In one embodiment of the present invention, the disperse red dye composition comprises, by weight percentage: 30% component A, 50% component B, and 20% component C.
[0018] The present invention also provides the application of the above-mentioned disperse red dye composition in the field of printing and dyeing polyester-ammonia blended fabrics.
[0019] Furthermore, the present invention also provides a method for dyeing polyester-ammonia blended fabrics in red, which uses the above-mentioned disperse red dye composition as the dye.
[0020] In one embodiment of the present invention, the red dyeing method specifically includes: (1) The disperse red dye composition is mixed with MF dispersant, sodium lignosulfonate and water, and ground to obtain disperse red dye solution; (2) The dispersed red dye solution was then used to dye the polyester-ammonia blended fabric.
[0021] In one embodiment of the present invention, in step (1), the pH of the dispersed red dye solution is adjusted to 12.
[0022] In one embodiment of the present invention, step (2) specifically includes: dyeing the polyester-ammonia blended fabric in a high sublimation fastness dispersed red dye solution, heating it for a period of time; then pre-drying it at 180°C and heat-setting it at 210°C.
[0023] In one embodiment of the present invention, in step (2), the bath ratio for dyeing is 1:20.
[0024] In one embodiment of the present invention, in step (2), the heating rate is 1.5℃ / min, and the maximum temperature is 130℃ and held for 40min.
[0025] In one embodiment of the present invention, in step (2), the polyester / spandex blended fabric can specifically be an 88% polyester / 12% spandex blended knitted fabric.
[0026] In the disperse red dye composition of this invention, based on the maximum ultraviolet absorption wavelength of the three components, component B, compared to component A, has an additional electron-withdrawing chlorine group at the right end of its structure. This results in a steric hindrance effect; that is, when Cl is introduced, it significantly repels the adjacent benzyl group. To alleviate this repulsion, the benzene ring is forced to twist, no longer maintaining complete coplanarity with the azo bond. The degree of conjugation decreases, the band gap increases, and a blue shift occurs in ultraviolet absorption. Therefore, the color is slightly lighter than component A. Similarly, component C, compared to component B, exhibits a blue shift, further lightening the color. In other words, the ultraviolet absorption wavelength is component A > component B > component C; therefore, component A has the deepest color, and component C has the lightest color.
[0027] In the disperse red dye composition of this invention, although conjugated distortion is detrimental to light absorption, for physical properties (sublimation fastness), the increased molecular weight of the chlorine atoms directly leads to a decrease in vapor pressure, making it more difficult to volatilize. Cl is a strongly electronegative atom, introducing a dipole moment. This increases dipole-dipole interactions between dye molecules in addition to van der Waals forces, making the molecules "grip tighter." Therefore, as long as the intermolecular binding forces (van der Waals forces + dipole forces) are strong enough, the sublimation fastness will improve. Therefore, in terms of sublimation fastness, component C ≥ component B ≥ component A.
[0028] In the disperse red dye composition of the present invention, each component is obtained by diazotization reaction of the corresponding intermediate with the diazo component; wherein, the intermediates involved in component A, component B and component C are intermediate A, intermediate B and intermediate C respectively, and the diazo component is 2,4-dinitroaniline to ensure that the hue is red; .
[0029] The synthetic routes for components A, B, and C are as follows: Figure 2 As shown.
[0030] Synthesis of intermediates A, B, and C corresponding to components A, B, and C: Synthesis of intermediate A: Benzyl chloride was used as the reaction solvent and reactant, and potassium carbonate was used as the acid-binding agent to react with aniline. After the reaction was completed, water was added and stirred until the salt was fully dissolved. The mixture was allowed to stand, and the aqueous layer was separated. Ethanol was added and stirred until all N,N-dibenzylaniline crystals precipitated. The mixture was then filtered, and the filter cake was soaked and washed with ethanol to obtain pure white crystals. The ethanol was recovered from the mother liquor under reduced pressure. The remaining liquid consisted of benzyl chloride and N-benzylaniline, which were used as raw materials for the next batch.
[0031] In the above reaction, the molar ratio of benzyl chloride to aniline is 3.5~5:1, the molar ratio of potassium carbonate to aniline is 2.1~2.5:1, the reaction temperature is 65~90℃, and the reaction time is 6~12h.
[0032] After the above reaction is completed, the mass ratio of water to potassium carbonate is 3~4:1, the mass ratio of ethanol used for separation to benzyl chloride is 1.5~2:1, and the amount of ethanol used for washing is measured according to the filter cake yield, which is about 1.5~2 times the mass of the filter cake.
[0033] Synthesis of intermediate B: Using ethanol as the reaction solvent, potassium carbonate and aniline were added, stirred, and heated to a certain temperature. Benzyl chloride was then added dropwise, and the reaction was maintained at this temperature for a period of time. Then, 4-chlorobenzyl chloride was added, and the temperature was further increased to reflux. After maintaining the temperature for a period of time, the mixture was allowed to cool naturally to room temperature. The mixture was then filtered, and the filtrate was removed. Ethanol was recovered under reduced pressure. The remaining residue consisted of benzyl chloride monosubstituted aniline and 4-chlorobenzyl chloride monosubstituted aniline, which were reserved for the next batch. The filter cake was soaked three times in deionized water to thoroughly remove salts, yielding intermediate B of N-benzyl-N-(4-chloro)benzylaniline.
[0034] In the above reaction, the molar ratio of benzyl chloride to aniline is 1~1.05:1, the molar ratio of 4-chlorobenzyl chloride to aniline is 1~1.05:1, the molar ratio of potassium carbonate to aniline is 2.05~2.1:1, and the amount of ethanol is 1.5~2 times the sum of the masses of aniline, benzyl chloride, 4-chlorobenzyl chloride, and potassium carbonate.
[0035] In the above reaction, benzyl chloride is added at a rate of 1 drop / 2 s, and the addition time is controlled between 1.5 and 2 hours. After the addition is complete, the reaction temperature is controlled between 65 and 70°C, and the reaction time is 5 to 6 hours.
[0036] In the above reaction, after adding 4-chlorobenzyl chloride, the reaction temperature was reflux temperature (78℃) and the reaction time was 12h.
[0037] Synthesis of intermediate C: Using ethanol as the reaction solvent, potassium carbonate, aniline, and 4-chlorobenzyl chloride were added, stirred, and heated to reflux temperature for 12-14 h. After the reaction was completed, the temperature was lowered to room temperature, filtered, and the filtrate was depressurized to recover ethanol. The remaining residue was 4-chlorobenzyl chloride and N-(4-chloro)chlorobenzyl aniline, which were reserved for the next batch. The filter cake was soaked in deionized water three times and filtered to obtain light green crystals.
[0038] In the above reaction, the molar ratio of 4-chlorobenzyl chloride to aniline is 2.05~2.1:1, the molar ratio of potassium carbonate to aniline is 2.1~2.2:1, and the amount of ethanol is 1.5~2 times the sum of the masses of 4-chlorobenzyl chloride, aniline, and potassium carbonate.
[0039] The reaction temperature in the above reaction is the reflux temperature of ethanol (78.3℃).
[0040] The synthesis of components A, B, and C: 2,4-Dinitrodiazotization: A measured amount of 98% concentrated sulfuric acid and 2,4-dinitroaniline were added to a four-necked flask. Stirring was started, and after the 2,4-dinitroaniline was completely dissolved, the temperature was lowered to -5~0℃. 40% nitrosyl sulfuric acid was then added dropwise. The temperature was strictly controlled during the addition to ensure it did not exceed 0℃. After the addition was completed, the temperature was maintained for 2 hours. The resulting diazo solution was used for the next coupling step.
[0041] In the above reaction, the mass of sulfuric acid is 2.5 to 4 times that of 2,4-dinitroaniline, and the molar ratio of nitrosylsulfuric acid to 2,4-dinitroaniline is 1.05 to 1.1:1.
[0042] Synthesis of Component A: Water, intermediate A, aminosulfonic acid, fatty alcohol polyoxyethylene ether, and OP-10 emulsifier were added to a four-necked flask. Stirring was started, and a small amount of sulfuric acid was added dropwise. The temperature was initially lowered to below 0°C, and diazonium solution was added dropwise, with strict temperature control during the addition. After the addition was complete, the mixture was kept at this temperature for several hours. Once the reaction was complete, the mixture was slowly heated to a certain temperature and kept at this temperature for 2 hours to allow the crystals of component A to grow. The mixture was then hot-filtered, and the filter cake was washed with hot water to obtain component A.
[0043] In the above reaction, the molar ratio of intermediate A to 2,4-dinitroaniline is 1.05~1.2:1, the amount of aminosulfonic acid is 0.5~1g (based on the amount of residual nitrosylsulfuric acid), fatty alcohol polyoxyethylene ether is used as a dispersant, accounting for about 0.5% of the total system mass, and OP-10 emulsifier is 1~2ml. The amount of water is controlled at 3.5~4 times the sum of the masses of the other components.
[0044] The reaction temperature is below 0℃, preferably -5 to -3℃.
[0045] After the above reaction is completed, the crystallization temperature is 65~70℃, and the crystallization time is maintained at about 2 hours.
[0046] Synthesis of Component B: Water, intermediate B, aminosulfonic acid, fatty alcohol polyoxyethylene ether, and OP-10 emulsifier were added to a four-necked flask. Stirring was started, and a small amount of sulfuric acid was added dropwise. The temperature was initially lowered to below 0°C, and diazonium solution was added dropwise, with strict temperature control during the addition. After the addition was complete, the mixture was kept at this temperature for several hours. Once the reaction was complete, the mixture was slowly heated to a certain temperature and kept at this temperature for 2 hours to allow the crystals of component B to grow. The mixture was then hot-filtered, and the filter cake was washed with hot water to obtain component B.
[0047] In the above reaction, the molar ratio of intermediate B to 2,4-dinitroaniline is 1.1~1.2:1, the amount of aminosulfonic acid is 0.5~1g (based on the amount of residual nitrosylsulfuric acid), fatty alcohol polyoxyethylene ether is used as a dispersant, accounting for about 0.5% of the total system mass, and OP-10 emulsifier is 1~2ml. The amount of water is controlled at 3.5~4 times the sum of the masses of the other components.
[0048] The reaction temperature is below 0℃, preferably -5 to -3℃.
[0049] After the above reaction is completed, the crystallization temperature is 70~85℃, and the crystallization time is maintained at about 2 hours.
[0050] Synthesis of Component C: Water, intermediate C, aminosulfonic acid, fatty alcohol polyoxyethylene ether, and OP-10 emulsifier were added to a four-necked flask. Stirring was started, and a small amount of sulfuric acid was added dropwise. The temperature was initially lowered to below 0°C, and diazonium solution was added dropwise, with strict temperature control during the addition. After the addition was complete, the mixture was kept at this temperature for several hours. Once the reaction was complete, the mixture was slowly heated to a certain temperature and kept at this temperature for 2 hours to allow the crystals of component C to grow. The mixture was then hot-filtered, and the filter cake was washed with hot water to obtain component C.
[0051] In the above reaction, the molar ratio of intermediate C to 2,4-dinitroaniline is 1.1~1.2:1, the amount of aminosulfonic acid is 0.5~1g (based on the amount of residual nitrosylsulfuric acid), fatty alcohol polyoxyethylene ether is used as a dispersant, accounting for about 0.5% of the total system mass, and OP-10 emulsifier is 1~2ml. The amount of water is controlled at 3.5~4 times the sum of the masses of the other components.
[0052] The reaction temperature is below 0℃, preferably -5 to -3℃.
[0053] After the above reaction is completed, the crystallization temperature is 70~85℃, and the crystallization time is maintained at about 2 hours.
[0054] The above reaction yielded components A, B, and C.
[0055] Beneficial effects: (1) The present invention found that by combining components A, B and C in a specific ratio, an unexpected synergistic effect was produced, which has the effect of synergistic enhancement.
[0056] Component A enhances the dark color effect of the dye and adjusts the polarity and molecular packing state of the dye. Although Component A is prone to staining when used alone at higher temperatures, its intermolecular forces are optimized when used in conjunction with Components B and C, effectively suppressing the phenomenon of high-temperature staining of spandex, while significantly improving the coloring rate at low temperatures.
[0057] Component B acts as an intermediate bridge, compensating for the insufficient color yield of component C, improving the overall color depth, and maintaining good wash fastness.
[0058] Component C provides an extremely high sublimation fastness framework, ensuring that it does not sublimate at a high temperature of 210°C.
[0059] (2) Excellent high temperature resistance: The disperse red dye composition provided by the present invention can achieve a sublimation fastness of 4-5 under heat setting conditions of 210℃, and has extremely low staining on spandex (grey card grade 4 or above), which solves the problem of color change of dark polyester spandex fabrics under heat setting.
[0060] (3) Excellent wet fastness: thanks to the chlorine atoms and specific N,N-substituents introduced into the molecular structure, the hydrophobicity of the dye is increased, making it more compatible with the hydrophobicity of the polyester / polyether of the spandex fiber, the dye and fiber are more tightly bonded, and the washing fastness is excellent. Attached Figure Description
[0061] Figure 1 The maximum ultraviolet absorption wavelengths of components A, B, and C are given.
[0062] Figure 2 This is the synthesis route for components A, B, and C.
[0063] Figure 3 These are hue photographs of the polyester-spandex blended fabric samples obtained in Examples 4-6 before and after sublimation.
[0064] Figure 4 The samples are the sublimated multifiber dyed fabrics from Examples 4-6.
[0065] Figure 5 Comparison of hue photographs and sublimation fastness results of polyester-spandex blended fabric samples obtained from different compositions in Example 7.
[0066] Figure 6 The 1H NMR spectrum of component A is shown.
[0067] Figure 7 The 1H NMR spectrum of component B is shown.
[0068] Figure 8 The 1H NMR spectrum of component C is shown. Detailed Implementation
[0069] The source of raw materials involved in this invention: 2,4-Dinitroaniline, benzyl chloride, 4-chlorobenzyl chloride, OP-10 emulsifier, and fatty alcohol polyoxyethylene ether were all purchased from Shanghai Maclean Biochemical Technology Co., Ltd.
[0070] Disperse Red 97 (CAS 12223-48-2) and Disperse Red UWA-3B are both from Yantai Chemical Technology Co., Ltd.
[0071] Dispersed Red 3R, based on the patent structure of Zhejiang Wanfeng Chemical Co., Ltd. (CN 121293779 A).
[0072] 98% sulfuric acid, 40% nitrosyl sulfuric acid, aminosulfonic acid, ethanol, potassium carbonate, sodium lignosulfonate, and dispersant MF were all purchased from Sinopharm Chemical Reagent Co., Ltd.
[0073] The present invention will be further described below with reference to specific embodiments.
[0074] Example 1 Synthetic intermediate A: 95g benzyl chloride, 62.4g potassium carbonate, and 20g aniline were added to a four-necked flask. Stirring was started, and the temperature was raised to 75-80℃. The reaction was maintained for at least 6 hours. TLC was used for monitoring (developing solvent: ethyl acetate: petroleum ether = 1:4). The reaction ended when the monosubstituted spots disappeared. 200g deionized water was added at this temperature, and the mixture was stirred for 0.5 hours. The mixture was poured into a separatory funnel, allowed to stand, and allowed to separate into layers. The lower aqueous phase was removed, and the resulting organic phase was poured into a four-necked flask. Stirring was started, and ethanol was slowly added. The mixture was stirred for at least 1 hour until all N,N-dibenzylaniline crystals precipitated. The crystals were filtered, and the filter cake was soaked and washed with ethanol to obtain pure white crystals. Vacuum drying yielded 55g of dried intermediate A. HPLC analysis showed a purity of 97.2%. Ethanol was recovered from the mother liquor under reduced pressure. The remaining liquid consisted of benzyl chloride and N-benzylaniline, which were used as raw materials for the next batch.
[0075] Diazotization of 2,4-dinitroaniline: 7.32 g of 2,4-dinitroaniline and 28 g of sulfuric acid were added to a four-necked flask. Stirring was started, and the 2,4-dinitroaniline was completely dissolved. The temperature was then lowered to below 0°C, and 14 g of 40% nitrosyl sulfuric acid was added dropwise. During the addition, the temperature was controlled not to exceed 0°C. After the addition was completed, the temperature was kept at that temperature for 2 hours to obtain approximately 49 g of diazo solution, which was then set aside for use.
[0076] Synthesis of Component A: 200g water, 14.2g intermediate A, 0.5g aminosulfonic acid, 2ml fatty alcohol polyoxyethylene ether, and 1ml OP-10 emulsifier were added to a four-necked flask. Stirring was started, and 1ml of sulfuric acid was added dropwise. The temperature was lowered to below 0℃, and 49g of the above-mentioned diazonium solution was added dropwise, with strict temperature control during the addition. After the addition was complete, the reaction was maintained for 8-10 hours. After the reaction was complete, the temperature was slowly heated to 70℃ and maintained for 2 hours to increase the crystal size of Component A. The mixture was hot-filtered, and the filter cake was washed with hot water until the filtrate was colorless and neutral, yielding dark red Component A. This was dried at 100℃ for 6 hours to obtain 17.2g of dried product. HPLC analysis showed a purity of 95.8%.
[0077] The 1H NMR spectrum of component A is shown below. Figure 6 As shown, 1¹H NMR (400 MHz, DMSO-d⁶) δ: 8.9 (s, 1H), 8.55 (dd, J=8.4Hz, 2H), 7.80 (d, J=8.1Hz, 2H), 7.45 (m, 8H), 6.75 (d, J=8.4Hz, 2H), 4.78 (s, 2H, -CH₂-). The ¹H NMR chemical shifts show that the number of hydrogen atoms and the chemical shifts of component A correspond to the target structure, confirming that the structure corresponding to component A was indeed synthesized.
[0078] Example 2 Synthesis of Intermediate B: 225 g ethanol, 62.4 g potassium carbonate, and 20 g aniline were added to a four-necked flask. Stirring was started, and the temperature was raised to 65 °C. 28.6 g benzyl chloride was then added dropwise, and the mixture was kept at this temperature for 6 hours after the addition was complete. Then, 36.35 g 4-chlorobenzyl chloride was added, and the mixture was heated to reflux and kept at this temperature for 12 hours. After the reaction was complete, the mixture was allowed to cool naturally to room temperature. The mixture was filtered, and the filtrate was removed. Ethanol was recovered under reduced pressure. The remaining residue consisted of benzyl chloride monosubstituted aniline and 4-chlorobenzyl chloride monosubstituted aniline, which were reserved for the next batch. The filter cake was soaked three times in deionized water to thoroughly remove salts, yielding intermediate B of N-benzyl-N-(4-chloro)benzylaniline. The product was dried under vacuum to obtain 62.2 g of dried intermediate B, with a purity of 96.5% as determined by HPLC.
[0079] Synthesis of component B: Referring to Example 1, intermediate A in Example 1 was replaced with 14.8g of intermediate B, the crystallization temperature was changed to 80℃, and the other conditions remained unchanged. Finally, 18.3g of red powder solid was obtained, and the purity was 95.2% as determined by HPLC.
[0080] The 1H NMR spectrum of component B is shown below. Figure 7 As shown, 1 ¹H NMR (400 MHz, DMSO-d⁶) δ: 8.88 (s, 1H), 8.54 (dd, J=8.4Hz, 2H), 7.76 (d, J=8.1Hz, 2H), 7.30 (m, 8H), 6.77 (d, J=8.1Hz, 2H), 4.78 (s, 2H, -CH₂-). The ¹H NMR chemical shifts show that the number of hydrogen atoms and the chemical shifts of component B correspond to the target structure, confirming that the structure corresponding to combination B was indeed synthesized.
[0081] Example 3 Synthesis of intermediate C: 220 g ethanol, 62.4 g potassium carbonate, and 72.7 g 4-chlorobenzyl chloride were added to a four-necked flask, stirred, and heated to reflux temperature (78.3 °C) for 12–14 h. After the reaction was complete, the mixture was cooled to room temperature, filtered, and the filtrate was used to recover ethanol under reduced pressure. The remaining residue contained 4-chlorobenzyl chloride and N-(4-chloro)chlorobenzylaniline, which were reserved for the next batch. The filter cake was soaked three times in deionized water, filtered, and light green crystals were obtained. After drying under reduced pressure, 70 g of the product was obtained, with a purity of 97.4% as determined by HPLC.
[0082] Synthesis of component C: Following Example 1, component A was replaced with 14.4 g of intermediate C, with all other conditions remaining unchanged, and 19.7 g of red powder was finally obtained, with HPLC detection of 96.3%.
[0083] The 1H NMR spectrum of component C is shown below. Figure 8 As shown, 1 ¹H NMR (400 MHz, DMSO-d⁶) δ: 8.89 (1, 1H), 8.54 (dd, J=8.4Hz, 2H), 7.76 (d, J=8.1Hz, 2H), 7.38 (m, 8H), 6.77 (d, J=8.1Hz, 2H), 4.79 (s, 2H, -CH₂-). The ¹H NMR chemical shifts show that the number of hydrogen atoms and the chemical shifts corresponding to component C correspond to the target structure, confirming that the structure corresponding to component C was indeed synthesized.
[0084] Example 4 A disperse red dye composition comprising component A, component B and component C: component A is 20%, component B is 50% and component C is 30%.
[0085] A method for preparing a dispersed red dye solution is as follows: Weigh out 0.2g of component A, 0.5g of component B, and 0.3g of component C dry powder respectively, add 1g of MF (sodium naphthalene sulfonate) dispersant and 0.5g of sodium lignosulfonate, add 5ml of water, grind until the particle size is <1.5μm, continue to add 92.5 mL of water to dilute, prepare 100ml of disperse red dye solution, and set aside for use.
[0086] The following is a method for dyeing polyester-ammonia blended fabrics red: Prepare a dye bath with a liquor ratio of 1:20 by taking 0.5 ml of disperse red dye solution and adjusting the pH to 12. Weigh 1 g of 88% polyester / 12% spandex blended knitted fabric. Follow the dyeing process: heating rate 1.5℃ / min, maximum temperature 130℃, and hold for 40 min.
[0087] Post-processing: Pre-bake at 180℃, heat set at 210℃ for 30 seconds.
[0088] Example 5 A disperse red dye composition was prepared according to Example 4, but the proportions of the components were adjusted so that component A was 20%, component B was 40%, and component C was 40%, while the other conditions remained unchanged.
[0089] The corresponding dispersed red dye solution was prepared according to the same process as in Example 4, and the polyester-ammonia blended fabric was dyed red.
[0090] Example 6 A disperse red dye composition was prepared according to Example 4, but the proportions of the components were adjusted so that component A was 10%, component B was 10%, and component C was 80%, while the other conditions remained unchanged.
[0091] The corresponding dispersed red dye solution was prepared according to the same process as in Example 4, and the polyester-ammonia blended fabric was dyed red.
[0092] Test Example 1 UV testing: Acetone was used to dissolve components at a uniform concentration. The maximum absorption wavelength λmax and molar extinction coefficient ε of components A, B, and C were measured using a UV-Vis spectrophotometer. (See attached image.) Figure 1 The results are summarized in Table 1: Table 1
[0093] Test Example 2 The fabric samples obtained in Examples 4 to 6 (see...) Figure 3 The data were tested using a Data Color 600 colorimeter, and the results are summarized in the table below. The fabric samples obtained in Examples 4 to 6 were pre-dried at 180°C and heat-set at 210°C to obtain sublimated fabric samples (see...). Figure 3 The data were then tested using a Data Color 600 colorimeter, and the results are summarized in Table 2 below. Table 2
[0094] Test results: Sublimation fastness (210℃ / 30s) (see...) Figure 4 ): Example 4, component A: component B: component C = 2:5:3 (mass percentage example), staining grade 4-5; Example 5, Component A: Component B: Component C = 2:4:4 (mass percentage example), staining grade 4-5; Example 6, Component A: Component B: Component C = 1:1:8 (mass percentage example), staining grade 5.
[0095] As can be seen from Examples 4 to 6, when the content of the high sublimation fastness component C is low, as in Example 4, trace amounts of dye escape from the fiber interior, causing slight staining. However, as the concentration of component C increases slightly, as in Example 5, the color depth K / S actually increases. This may be because, immediately after dyeing, the dye molecules in the amorphous region of the polyester fiber may be in a relatively disordered and loose state. During high-temperature sublimation testing (such as dry heat treatment at 210°C), the heat provides activation energy, causing the dye molecules remaining inside the fiber to undergo thermal rearrangement, forming more compact aggregates or microcrystals. This ordered arrangement often leads to a red shift in the absorption spectrum or an increase in the molar absorptivity. In other words, with the same number of dye molecules, after being arranged neatly, the ability to "absorb light" is stronger, which macroscopically manifests as a deeper color (increased K / S). In Example 6, the further increase in the high sublimation fastness component C resulted in a more significant increase in the K / S value.
[0096] Therefore, it can be seen that the color of Example 5 is slightly lighter than that of Example 4, but the sublimation fastness is improved. The color of Example 6 is even lighter, but the sublimation fastness can withstand a high temperature of 210°C, making it particularly suitable for outdoor functional fabrics with extremely high heat resistance requirements.
[0097] Comparative Example 1 Several other dyes shown in Table 3 below were used as comparative examples: Table 3
[0098] Referring to the dyeing process in Example 4, the three dyes were used to dye polyester-spandex blended fabrics, and the resulting fabric samples were subjected to sublimation tests. The results are shown in Table 4 below: Table 4
[0099] The three dyes mentioned above have bright colors and high dyeing rates, but poor sublimation fastness. Disperse Red 3R performs well at 180℃, but its sublimation fastness decreases as the temperature increases.
[0100] Example 7 Referring to Example 4, components A and B were mixed and dyed at mass ratios of 3:7, 4:6, and 5:5, respectively, with other parameters remaining unchanged. The resulting fabric samples are shown below. Figure 5 As shown.
[0101] Depend on Figure 5 The results show that it performs well at 180℃, but when heat-set at 210℃, due to the lack of high heat-resistant skeleton support from component C, the overall sublimation fastness drops to grade 3, and obvious spandex staining occurs.
[0102] Example 8 Referring to Example 4, the mass ratio of component A, component B, and component C in the composition was adjusted (as shown in Table 5), while other aspects remained unchanged.
[0103] Table 5
[0104] Component C is key to improving sublimation fastness, but excessive addition will inhibit dye uptake (leading to a decrease in the K / S value). In order to obtain excellent heat resistance without sacrificing color yield, there is an upper limit threshold for the amount of component C added, which is no more than 80%.
[0105] Comparative Example 2 A dispersible red dyeing solution: Weigh 1.0g of component A dry powder, add 1g of MF (sodium naphthalene sulfonate) dispersant and 0.5g of sodium lignosulfonate, add water, grind until the particle size is <1.5μm, continue to dilute with water, and prepare 100ml of dispersible red dyeing solution I for later use.
[0106] A dispersible red dyeing solution: Weigh 1.0g of component B dry powder, add 1g of MF (sodium naphthalene sulfonate) dispersant and 0.5g of sodium lignosulfonate, add water, grind until the particle size is <1.5μm, continue to dilute with water, and prepare 100ml of dispersible red dyeing solution II for later use.
[0107] A dispersible red dyeing solution: Weigh 1.0g of component C dry powder, add 1g of MF (sodium naphthalene sulfonate) dispersant and 0.5g of sodium lignin sulfonate, add water, grind until the particle size is <1.5μm, continue to dilute with water, and prepare 100ml of dispersible red dyeing solution III for later use.
[0108] The fabric samples were obtained by applying the above dye solution as described in Example 4, and the results are shown in Table 6.
[0109] Table 6
[0110] Combining the results in Tables 5 and 6, component C contributes significantly to sublimation fastness (reaching grade 5 at all temperatures in the 0.5:0.5:9 formulation of Example 8). However, when the proportion of component C decreases to a certain level (e.g., 1:1:8 in Example 8), the sublimation fastness drops noticeably. Therefore, component C is the core of sublimation stability, but there is an upper limit to the amount of component C added; it is best not to exceed 80%. Adding more than 80% will result in insufficient color depth. Based on the previous results, component A drives the dark color performance and is key to achieving high dark color. Component B, through its intermediate proportion, achieves a balance between sublimation fastness and dark color performance, ensuring that the system takes into account both thermal stability and color depth. This functional division reflects the compounding principle of "complementary performance and synergistic effect" between components.
[0111] The data above shows that the embodiments of the present invention can perform dyeing at high pH without the need for reduction washing. According to the technical solution and corresponding test data provided by the present invention, the high sublimation fastness disperse red dye composition for polyester-ammonia blended fabrics provided by the present invention demonstrates the superior and unique characteristics of the dye provided by the present invention in dyeing polyester-ammonia blended fabrics, particularly in terms of wide pH range dyeing, dyeing rate, and high sublimation fastness.
[0112] The embodiments provided above are not intended to limit the scope of the invention, nor are the described steps intended to limit the order of execution. Any obvious modifications made to the invention by those skilled in the art based on existing common knowledge also fall within the scope of protection defined by the claims.
Claims
1. A disperse red dye composition with high sublimation fastness for polyester-ammonia blended fabrics, characterized in that, The composition comprises at least two of the following disperse dyes: component A, component B, and component C; Component A is an N,N-dibenzylamine azo disperse dye with the following structure: ; Component B is an N-benzyl-N-(4-chloro)benzylamine azo disperse dye with the following structure: ; Component C is an N,N-bis(4-chloro)benzylamine azo disperse dye with the following structure: .
2. The high sublimation fastness disperse red dye composition for polyester-ammonia blended fabrics according to claim 1, characterized in that, The disperse red dye composition comprises component A, component B and component C; wherein, by mass percentage, component A is 10%~40%, component B is 10%~70%, and component C is 10%~80%.
3. The high sublimation fastness disperse red dye composition for polyester-ammonia blended fabrics according to claim 1, characterized in that, The disperse red dye composition comprises component A, component B and component C; wherein, by mass percentage, component A is 10%~40%, component B is 10%~50%, and component C is 20%~80%.
4. The high sublimation fastness disperse red dye composition for polyester-ammonia blended fabrics according to claim 1, characterized in that, The disperse red dye composition comprises, by weight percentage: 20% component A, 50% component B, and 30% component C; or 20% component A, 40% component B, and 40% component C.
5. The high sublimation fastness disperse red dye composition for polyester-ammonia blended fabrics according to claim 1, characterized in that, The disperse red dye composition comprises, by weight percentage: 40% component A, 30% component B, and 30% component C; or 30% component A, 50% component B, and 20% component C.
6. The high sublimation fastness disperse red dye composition for polyester-ammonia blended fabrics according to claim 1, characterized in that, The disperse red dye composition, by mass percentage, comprises the following: 10% component A, 10% component B, 80% component C.
7. The application of the high sublimation fastness disperse red dye composition for polyester-ammonia blended fabrics according to any one of claims 1-6 in the field of printing and dyeing polyester-ammonia blended fabrics.
8. A method for dyeing polyester-ammonia blended fabrics red, characterized in that, The dye is a disperse red dye composition with high sublimation fastness for polyester-ammonia blended fabrics as described in any one of claims 1-6.
9. The red dyeing method according to claim 8, characterized in that, The red staining method specifically includes: (1) The high sublimation fastness disperse red dye composition is mixed with MF dispersant, sodium lignosulfonate and water, and ground to obtain disperse red dye solution; (2) The dispersed red dye solution was then used to dye the polyester-ammonia blended fabric.
10. The red dyeing method according to claim 9, characterized in that, Step (2) specifically includes: dyeing the polyester-ammonia blended fabric in a high sublimation fastness dispersed red dye solution and heating it for a period of time; then pre-drying it at 180°C and heat-setting it at 210°C.
Citation Information
Patent Citations
Disperse red dye monomer, and preparation method, composition and application thereof
CN121293779A
Reduction-cleaning-free black disperse dye and dyeing method thereof
CN121293782A
Dispersed dark blue to black dye composition and application thereof
CN122011802A